2007
DOI: 10.3354/meps336161
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the North Equatorial Current on the population genetic structure of Tridacna crocea (Mollusca: Tridacnidae) along the eastern Philippine seaboard

Abstract: Tridacna crocea populations were sampled from 15 locations throughout the eastern Philippine seaboard and screened for allozyme variation at 7 polymorphic loci in order to examine the influence of the North Equatorial Current (NEC) bifurcation on population genetic structure. Significant genetic differentiation among all populations was detected (F ST = 0.065). Ordination methods and cluster analysis revealed 2 regional groups and a north-south spatial genetic structure broadly concordant with the bifurcation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 25 publications
6
32
1
1
Order By: Relevance
“…In other words, geographical isolation is not the factor in structuring biogeographical gradients of genetic diversity in S. thunbergii . As expected, homogeneous populations in the NWP driven by oceanic currents have also been reported in marine invertebrates from that area, such as the clam Tridacna crocea (Ravago‐Gotanco et al ., ), the crab Clistocoeloma sinense (Yuhara et al ., ) and the snail Batillaria attramentaria (Ho et al ., ). Sargassum thunbergii populations along the Japan‐Pacific side are characterized by extremely low genetic differentiation (ITS2: F ST = −0.04 to 0.01; cox 3: F ST = 0.00–0.06), which can be ascribed to the interactive coastal hydrodynamic systems (Fujikura et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, geographical isolation is not the factor in structuring biogeographical gradients of genetic diversity in S. thunbergii . As expected, homogeneous populations in the NWP driven by oceanic currents have also been reported in marine invertebrates from that area, such as the clam Tridacna crocea (Ravago‐Gotanco et al ., ), the crab Clistocoeloma sinense (Yuhara et al ., ) and the snail Batillaria attramentaria (Ho et al ., ). Sargassum thunbergii populations along the Japan‐Pacific side are characterized by extremely low genetic differentiation (ITS2: F ST = −0.04 to 0.01; cox 3: F ST = 0.00–0.06), which can be ascribed to the interactive coastal hydrodynamic systems (Fujikura et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, results from giant clam genetic studies have indicated restricted gene flow, suggesting lower levels of exchange [17], [18]. Ocean current patterns have been invoked to explain such genetic divergences among marine invertebrate populations [19], as they can influence temporal and spatial physical processes that potentially restrict larval dispersal and gene flow [20], [21].…”
Section: Introductionmentioning
confidence: 99%
“…crocea throughout Wallacea using mitochondrial (mtDNA) markers [24][25][26], allozymes [27,28], and microsatellites [29]. Both T. crocea and T. maxima have been shown to contain distinct mtDNA clades associated with Sumatra (Sunda), Wallacea, and northwest New Guinea (Sahul, particularly in Cenderawasih Bay) [24][25][26].…”
Section: Discussionmentioning
confidence: 99%